Low Dose Chronic Angiotensin II Induces Selective Senescence of Kidney Endothelial Cells - Khan, Irfan; Schmidt, Marcel O.; Kallakury, Bhaskar; Jain, Sidharth; Mehdikhani, Shaunt; Levi, Moshe; Mendonca, Margarida; Welch, William; Riegel, Anna T.; Wilcox, Christopher S.; Wellstein, Anton (Frontiers in Cell and Developmental Biology, 2021)
Angiotensin II can cause oxidative stress and increased blood pressure that result in long term cardiovascular pathologies. Here we evaluated the contribution of cellular senescence to the effect of chronic exposure to low dose angiotensin II in a model that mimics long term tissue damage. We utilized the INK-ATTAC (p16Ink4a - Apoptosis Through Targeted Activation of Caspase 8) transgenic mouse model that allows for conditional elimination of p16Ink4a -dependent senescent cells by administration of AP20187. Angiotensin II treatment for 3 weeks induced ATTAC transgene expression in kidneys but not in lung, spleen and brain tissues. In the kidneys increased expression of ATM, p15 and p21 matched with angiotensin II induction of senescence-associated secretory phenotype genes MMP3, FGF2, IGFBP2, and tPA. Senescent cells in the kidneys were identified as endothelial cells by detection of GFP expressed from the ATTAC transgene and increased expression of angiopoietin 2 and von Willebrand Factor, indicative of endothelial cell damage. Furthermore, angiotensin II induced expression of the inflammation-related glycoprotein versican and immune cell recruitment to the kidneys. AP20187-mediated elimination of p16-dependent senescent cells prevented physiologic, cellular and molecular responses to angiotensin II and provides mechanistic evidence of cellular senescence as a driver of angiotensin II effects.